STUDY ETHNOMATHEMATICS: CLASSIFICATION OF GEOMETRICAL ASPECTS OF TRADITIONAL WOVEN FABRICS IN INDONESIA BY ORNAMENTAL GROUPS - WIDIANA (NIM: 90116007), ERINA
The design of Indonesian traditional weaving motif is very rich in variety. Generally the symbols used reflect deeply philosophical-religious values among others concerning human relationships with the universe. Many of these motives are geometrical symmetry. In the study, we tried to look at the motif design classification based on ornamental group symmetry. Based on translational isometric, the ornamental group is divided into three big groups namely, rosette, frieze and wallpaper. Research materials were taken from literature review and interviews with weavers in the village of Sukarare, Lombok, West Nusa Tenggara. The results of the interviews show that the design diversity is derived from traditions from generation to generation and has its own meaning. In the literature review, the grouping of designs based on their origin, produces 12 groups are Bali, Jawa, Flores, Kalimantan, Lombok, Maluku, Sabu, Sumatera, Sulawesi, Sumba, Sumbawa, and Timor. The study showed that the rosette group used in the design of motives of woven fabrics was a rosette group of type C_1,C_2,C_4,D_1,D_2,D_4,D_6, and D_7. And for frieze, all (seven) frieze groups have been used. But of the 17 wallpaper groups, 10 already used are W_1,W_2,W_1^1,W_1^2,W_1^3,W_2^1,W_2^2,W_2^3,W_4^1, and W_6. Then the classification is also done by taking into account the color. Research is limited to the use of two colors and three colors. What is interesting is the rosette group C_3 and C_5 are quite popular apparently not in use. Although the weavers can make the motives of both groups. But the level of difficulty is higher and the time required is also longer.